Physical examination training for pharmacy residents in adult patient care programs: A survey of program directors. Issue 5 (20th May 2019) - Watson, Kristin; Leon, Nicholas; Reed, Brent N.; Levit, Matthew B.; Devabhakthuni, Sandeep
Abstract: Purpose: To determine the type and frequency of formalized (structured education developed to meet a set of predefined goals and provide educational content and learning materials) and nonformalized physical examination (PE) training offered to pharmacy residents in adult patient care‐focused residency programs in the United States and Puerto Rico. Methods: A survey was distributed to a random sample of 1000 postgraduate year one and two adult patient care residency program directors. Participants were queried to determine if they offered PE training and the types of training offered. Barriers to and reasons for not providing PE training were assessed. Descriptive statistics were performed. Results: There were 122 respondents. Thirteen (10.7%) programs provide formalized PE training and six of these were postgraduate year 1 residencies (46.2%). Informal PE training resources were provided in 97/117 (82.9%) programs. The duration and scope of training programs varied. Forty‐four of 116 (37.9%) responding programs required components of the PE in one or more rotations. The most commonly cited reasons for those who have not considered a formalized training program ( n = 94) were that performing a PE is not part of the residency program (56.4%), lack of perceived value (45.7%), that PE is not part of the practice of the organization (43.6%), lack of trained clinicians (35.1%), lack of awareness that this type of training is available (35.1%), and lack of time in the schedule (31.9%) (respondents were able to select more than one). Conclusion: Many pharmacy organizations endorse PE, yet formalized PE training does not appear to be routinely offered in adult patient care‐focused residency programs. Reasons for not offering a formalized training program suggest that raising awareness of the benefits of pharmacists learning PE is warranted. As pharmacists seek provider status, the need to increase PE training in pharmacy residency programs may be necessary.